Improving Speaking Fluency of The 7th Graders Students Through The Communicative Approach In SMPN 1 Tenggarong - Dwi Panria Irianti; Ikhwanul Ahsan Faryabi Muja (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
The study was about improving speaking fluency of the students by teaching them using communicative approach. The objective of the study was to find out: 1. How the communicative approach improved the students’ speaking fluency, 2. How the perception of the students about communicative approach.This research was conducted by using CAR (Classroom Action Research). This research had two cycles. There were nine classes of the seventh graders in SMPN 1 Tenggarong. The writers chose one class as the subject that had a middle level ability of speaking English. After the first cycle, the students were given a test. After the scores out, the treatment was applied by the writers. To see whether it was successful or not, the writers themselves gave the post-test. Then the writers did the same thing like on the first cycle for the next cycle. The writers also gave an interview with an open-ended question to find out the students’ perception of communicative approach. The result showed that there was increased in their speaking fluency. In the first cycle, the score was 75,45 and 77,30. In the second cycle, the score was 79,6 and 81,60. Secondly, the perception of the students toward communicative approach showed that the students had a positive relationship with the teacher and the other students and also had a better cooperation in the class. It also showed how the students became more active in the classroom.